An evaluation of the selected mathematical competence of the first-year students of economic studies - Kopańska-Bródka, Donata; Dudzińska-Baryła, Renata; Michalska, Ewa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
In Poland, since 1985 when the matura exam in mathematics was no longer compulsory, low-level of math skills and poor learning results have been constantly talked about. The academic community warned that young people were massively avoiding the technical, mathematical fields of study and fields with mathematics as a compulsory subject. We are seeing a constantly decreasing level of mathematical knowledge of first-year students, and sometimes even their ignorance of the elementary issues, basic concepts or an awkwardness in performing calculations. The situation would radically change after the reintroduction of the compulsory matura exam in mathematics in 2010. This article presents the results of the evaluation of the mathematical competence of students (who were obliged to pass the matura exam in mathematics). The evaluation was carried out every year at the beginning of the first year of the economic undergraduate studies during 2012-2014. We have analyzed the level of mathematical competence in the area of knowledge and skills over the subsequent years as well as the knowledge of selected content from the core curriculum of mathematics taught in upper-secondary schools.
Didactics of Mathematics, 2015, Nr 12 (16), s. 69-84
Keywords: mathematical competence; student assessment; questionnaire survey